TITLE THE EMBODIMENT OF UBUNTU PHILOSOPHY IN FOSTERING EMPATHY AND COMPASSION IN SOCIAL WORK PRACTICE - Phoke Alpha Rakgwata; Ms Ramothwa JS (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The Ubuntu philosophy, a rich African worldview that emphasizes humanity's holistic nature, interconnectedness, and communal values, has significant ramifications for social work practice, especially when it comes to developing empathy and compassion. Ubuntu, which has its roots in the African idea of "I am because we are," encourages social workers to see people as essential members of a larger community rather than just as separate individuals. This interconnectedness forms the foundation for enhancing empathy and compassion among practitioners, which are critical elements in effective social work. Social work, as a profession oriented towards the welfare of others, benefits from exploring this philosophy’s principles to enhance caregiving practices. Research findings has shown that through the adoption of Ubuntu's fundamental principles, social workers practice holistic, community-based work that empowers clients, advances social justice, and improves long-term health. The study aim was to investigate the role of Ubuntu philosophy in fostering empathy and compassion in social work practice. It also aims to assess the potential effectiveness of integrating Ubuntu principles in social work education and training. The study carried out comprehensive desktop electronic research to gather data and themes from previous research. All the research's sources were properly referenced in accordance with APA guidelines to give credit to the original authors and their contributions and ensure ethical consideration in the study.